Transformasi Peran Guru pada Pembelajaran Digital: Studi Budaya Mengajar di Kelas Modern - Ahmad Hilman Sidiq; Neng Dewi Hasanah; Muhammad Fadlullah Wijaya; Imam Solihin (PT. Panca Publishing Indonesia, 2026)
The digital transformation has fundamentally altered the role of teachers in modern learning environments. This study explores how teacher teaching culture changes alongside the adoption of digital technology in classrooms. Employing a qualitative approach with an ethnographic method, the research was conducted with 20 teachers from various educational levels across four major cities in Indonesia. Data were collected through participatory observation, in-depth interviews, and document analysis over eight months. The findings reveal four key themes: a shift in teacher role from transmitter to learning facilitator; technology-based adaptation of teaching culture; challenges in teacher digital competency; and reconstruction of teacher-student relationships in the digital ecosystem. This study concludes that teacher role transformation is not merely technical in nature but deeply touches cultural and pedagogical dimensions.